2017
DOI: 10.3390/ijerph14060655
|View full text |Cite
|
Sign up to set email alerts
|

Association of Education and Smoking Status on Risk of Diabetes Mellitus: A Population-Based Nationwide Cross-Sectional Study

Abstract: Background: Exposure to smoke, including environmental tobacco smoke (ETS), is a well-known risk factor for diabetes. Low socioeconomic status, especially lack of education, is also a risk factor for diabetes. Therefore, we assessed the association of demographic, socioeconomic, clinical, and behavior risk factor-related variables and smoking status, including ETS exposure, with the prevalence of diabetes. Methods: Data were from the 2007–2013 Korea National Health and Nutritional Evaluation Survey (KNHANES). … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…As proven in many longitudinal studies, smoking is a definite major risk factor of many cardiovascular diseases, including hypertension, myocardial infarction, and stroke [ 8 9 10 11 12 ]. Several studies have shown valid association between smoking and DM [ 13 14 15 16 ]. However, direct causal association between the two in Asian population has not been reported, although smoking rates are higher in Asians compared to those in Caucasians.…”
Section: Introductionmentioning
confidence: 99%
“…As proven in many longitudinal studies, smoking is a definite major risk factor of many cardiovascular diseases, including hypertension, myocardial infarction, and stroke [ 8 9 10 11 12 ]. Several studies have shown valid association between smoking and DM [ 13 14 15 16 ]. However, direct causal association between the two in Asian population has not been reported, although smoking rates are higher in Asians compared to those in Caucasians.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies have shown that diets characterized by high consumption of fruits and vegetables, whole grains, fish and poultry and by a decrease in consumption of red and processed meats, high-fat dairy products, processed foods [3] [4] and sugary drinks can reduce the risk of type 2 diabetes in the general population by 20% [5]. Smoking status and even exposure to a smoking environment are associated with an increased risk of type 2 diabetes [6]. However, moderate alcohol consumption would have a protective effect on type 2 diabetes [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, the results from studies on the effects of passive smoking on the prevalence of prediabetes and T2DM have been inconsistent. Some studies suggest that passive smoking can worsen carbohydrate and lipid metabolism disorders and promote the occurrence of T2DM [22][23][24], whereas other studies found that passive smoking had no effect on carbohydrate and lipid metabolism [8,24]. However, so far, there has been no study on the relationship between the duration of passive smoking and the prevalence of prediabetes and T2DM.…”
Section: Discussionmentioning
confidence: 99%